Therapeutic Effects of Silibinin Against Polycystic Ovary Syndrome Induced by Letrozole in Rats via Its Potential Anti-Inflammatory and Anti-Oxidant Activities - Marouf BH; Ismaeel DO; Hassan AH; Ali OJ (Dove Medical Press, 2022)
Bushra Hassan Marouf,1 Dana Omer Ismaeel,2 Ali Hussein Hassan,3,4 Othman Jalal Ali5,6 1Department of Pharmacology and Toxicology- College of Pharmacy, University of Sulaimani, Sulaimani, Kurdistan Region, Iraq; 2Department of Surgery and Theriogenology- College of Veterinary Medicine, University of Sulaimani, Sulaimani, Kurdistan Region, Iraq; 3Department of Basic Sciences- College of Dentistry, University of Sulaimani, Sulaimani, Kurdistan Region, Iraq; 4Department of Medical Laboratory Sciences- Komar University of Science and Technology, Sulaimani, Kurdistan Region, Iraq; 5Department of Surgery and Theriogenology- College of Veterinary Medicine- University of Sulaimani, Sulaimani, Kurdistan Region, Iraq; 6Department of Anaesthesia, College of Health Science, Cihan University of Sulaimaniya, Sulaimani, Kurdistan Region, IraqCorrespondence: Bushra Hassan Marouf, Department of Pharmacology and Toxicology, College of Pharmacy, University of Sulaimani, Sulaimani, 46001, Kurdistan Region, Iraq, Tel +964 7701562796, Email bushra.marouf@univsul.edu.iqBackground: Current therapies for polycystic ovary syndrome (PCOS) are accompanied by unwanted effects. Silibinin; a flavonolignan has pleiotropic activities and favorable safety profile.Purpose: To investigate the efficacy of silibinin on estrous cyclicity, inflammation, oxidative stress and ovarian morphology in letrozole-induced PCOS in rats.Methods: Forty-eight female Wistar albino rats were divided into 2 sets. Rats of the first set (n = 12), assigned as a negative control (NC) received only the vehicle, rats of the second set (n = 36), assigned as PCOS rats, were given letrozole 1mg/Kg orally for 21 days. On day 21, six rats from the first set and six rats from the second set were euthanized for confirmation of PCOS-induction. The remaining animals from the first set assigned as group 1, those in the second set (n = 30) were equally divided into 5 groups and treated daily for 19 days as follows: group 2 (positive control) received only the vehicle, group 3 treated with metformin 300mg/Kg orally, groups 4 and 5 treated respectively with 100 and 200 mg/Kg silibinin intraperitoneally (IP), and group 6 treated with a combination of metformin 300mg/Kg orally and silibinin 100mg/Kg IP. On day 40, blood samples were examined for luteinizing hormone (LH), testosterone (TS) and estradiol (EST) levels, the anti-inflammatory and antioxidant parameters, ovarian and uterine morphology.Results: Silibinin alone or in combination with metformin was found to be effective in restoring the regularity of estrous cycle by ameliorating the abnormal alterations of LH, TS, EST, tumor necrosis factor (TNF)-α, and oxidative status and by resuming the appearance of corpora lutea and decreasing or even total absence of cystic follicles in the ovaries.Conclusion: Silibinin was effective in restoring estrous regularities and alleviating hormonal and histomorphological abnormalities of the ovarian and uterine tissues, this could be due to its anti-androgenic, anti-inflammatory and antioxidant properties.Keywords: inflammation, estrous cycle, PCOS, silybin, testosterone